Essentials of nucleic acid analysis a robust approach - Keer, Jacquie T.; Birch, Lyndsey (Royal Society of Chemistry, 2008)
Over the last decade there has been a rapid development of molecular techniques, with an increasing range of instrumentation now available. The development of accompanying reference literature has not kept pace with technological advances and this poses significant challenges to the analyst. Essentials of Nucleic Acid Analysis sets out to guide the analyst through the steps needed to obtain good quality results in DNA analysis. The underlying principles for achieving this goal were formulated by LGC (formerly the Laboratory of the Government Chemist) as the six principles for ensuring valid analytical measurement, which are detailed in the introduction. The reader is also provided with guidelines for method validation and quality control of established and emerging DNA measurement techniques. The authors of each chapter are practitioners of the art of DNA analysis in areas where the quality of the result is critical. Technical details and examples of application of key techniques in nucleic acid analysis are provided while highlighting best practice, available standards and practical advice on improving measurement quality. This book provides an indispensable handbook and premier reference for those working in the widely varying areas and specifically in the fields of food analysis and forensic applications.
Keywords: Nucleic acids -- Analysis.; elektronické knihy; electronic books